Corrigendum to "Occurred Facial Pain during Acupotomy at a Site 5 pun Left of GV16: A Case Report" [J Acupunct Res 2024;41(1):69-73] - Eun Ju Lee; Tae Kyung Kim; Chang Min Shin; Jong Cheol Seo; Seo Hwi Kim; Si Yong Cho; Hyun Min Yoon; Cheol Hong Kim (MEDrang Inc., 2024)
The authors regret a mistake in the name of the author, Seo Hwi Kim, which was incorrectly stated as Seo Whi Kim. This has been corrected in this corrigendum and original file has been modified also. The authors would like to apologize for any inconvenience caused.